2016
DOI: 10.1371/journal.pone.0161003
|View full text |Cite
|
Sign up to set email alerts
|

Raised FGF-21 and Triglycerides Accompany Increased Energy Intake Driven by Protein Leverage in Lean, Healthy Individuals: A Randomised Trial

Abstract: A dominant appetite for protein drives increased energy intake in humans when the proportion of protein in the diet is reduced down to approximately 10% of total energy. Compensatory feeding for protein is apparent over a 1–2 d period but the mechanisms driving this regulation are not fully understood. Fibroblast growth factor-21 (FGF-21) has been identified as a candidate protein signal as levels increase in the circulation when dietary protein is low. The aim of this randomised controlled trial was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Diets low in protein have also been shown to elevate hepatic and plasma FGF21 levels in rodents and humans (Laeger et al 2014;Ozaki et al 2015;Gosby et al 2016;Pezeshki et al 2016;Pérez-Martí et al 2017). However, when decreasing the proportion of the diet derived from one nutrient in an isocaloric paradigm the proportion of another must increase and some studies are complicated by their concomitant higher sugar and carbohydrate content.…”
Section: Low-protein Diets In Combination With High Carbohydrate Maximentioning
confidence: 99%
“…Diets low in protein have also been shown to elevate hepatic and plasma FGF21 levels in rodents and humans (Laeger et al 2014;Ozaki et al 2015;Gosby et al 2016;Pezeshki et al 2016;Pérez-Martí et al 2017). However, when decreasing the proportion of the diet derived from one nutrient in an isocaloric paradigm the proportion of another must increase and some studies are complicated by their concomitant higher sugar and carbohydrate content.…”
Section: Low-protein Diets In Combination With High Carbohydrate Maximentioning
confidence: 99%
“…Applications of this approach to many species suggest that animals may eat food primarily to achieve a target intake of protein (Felton et al, 2009;Hawley et al, 2016;Raubenheimer and Simpson, 1997), which may be driven in part by fibroblast growth factor (FGF) signaling (Gosby et al, 2016). This contrasts the classical interpretation that food intake serves primarily to match energy demands.…”
Section: Introductionmentioning
confidence: 99%
“…Other patterns are possible and would require more complex fitting procedures. The leveraging of total intake by protein has been widely supported by empirical observations in a wide range of animals from insects to non-human primates (Felton et al, 2009;Gosby et al, 2016;Hawley et al, 2016;Raubenheimer and Simpson, 1997) and humans (Gosby et al, 2011;Martens et al, 2013;Martinez-Cordero et al, 2012;Simpson et al, 2003), although the percentage contribution of protein leverage to total intake has generally not been quantified as explicitly as indicated by the above approach. Nevertheless, protein leverage is increasingly being used to understand aspects of comparative feeding biology and the human obesity epidemic (Bekelman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The protein leverage hypothesis postulates that dietary protein restriction elicits a compensatory increase in calorie intake (hyperphagia) to achieve protein requirements . The authors and others reported that mild protein restriction increases caloric intake in rodents and in some, but not in all human studies . Most studies assessing the effects of protein restriction on energy balance formulated isocaloric diets by substituting protein with carbohydrate, while keeping fat concentration constant;; whether the hyperphagic and metabolic responses to protein restriction are due to a reciprocal increase in carbohydrate content is largely unknown.…”
Section: Introductionmentioning
confidence: 99%